Closed Fracture of The Proximal One-Third of The Left Femur in The Elderly: A Case Report - Yasmin Fadhilah Ardiyati; Syarif Hidayatullah; Rahmawati; Andi Firman Mubarak; Suciati Damopolii (International Medical Journal Corp. Ltd, 2025)
Background: A fracture of the proximal one-third of the femur is a serious musculoskeletal injury commonly found in the elderly due to osteoporosis and low-energy trauma, and in younger individuals as a result of high-energy trauma. This fracture involves the upper part of the thigh bone, including the femoral neck, intertrochanteric, and subtrochanteric regions, which play a vital role in supporting body weight and enabling movement. Case Report: Mrs. S, a 63-year-old woman, presented to the Emergency Department of Sayang Rakyat Regional Hospital after falling from a height of over 2 meters. The patient complained of severe pain in the left thigh with restricted mobility. Physical examination revealed deformity, swelling, and tenderness in the left femoral region, without neurovascular impairment. Radiological findings confirmed a closed fracture of the proximal one-third of the left femur. The diagnosis was established as closed fracture of the proximal one-third of the left femur (os femur sinistra). The patient was scheduled for open reduction and internal fixation (ORIF) and was given intravenous therapy consisting of Ketorolac and Ranitidine. Result: The patient underwent ORIF with good internal fixation results and no postoperative complications. The patient’s condition remained stable and early mobilization and rehabilitation were initiated. Conclusion: Proximal femur fractures in the elderly require prompt and appropriate management to prevent complications and restore lower limb function. ORIF remains the primary surgical treatment of choice and yields favorable outcomes when combined with optimal rehabilitation.